Faktor-faktor yang Memengaruhi Menarche Dini pada Remaja Perempuan - Hafizha, Syifa; Angraini, Dian Isti; Mayasari, Diana; Perdani, Roro Rukmi Windi (Medula, 2024)
Adolescence is a critical phase of rapid growth characterized by the maturation of reproductive organs, known as puberty. In females, puberty is marked by the onset of menstruation, with menarche being the first occurrence of menstruation, typically between the ages of 12 and 14 years. However, the average age of menarche in Indonesia has declined over the years, leading to an increase in early menarche cases. Early menarche occurs at an age of < 11 years (9-10 years) that is primarily driven by elevated estrogen levels in the female body. Factors influencing early menarche include genetics, nutritional status, lifestyle, dietary intake, physical activity, stress management, socioeconomic conditions, sexual behavior, and media exposure. This literature review aims to examine the correlation between these factors and the decreasing age of menarche among adolescent girls in Indonesia. Nutritional status and imbalanced dietary patterns are external factors strongly associated with early menarche. Genetic factors, particularly maternal menarche age, significantly influence the likelihood of early menarche in daughters. Low levels of physical activity contribute to increased ovarian activity and elevated estrogen levels, thereby raising the risk of early menarche. Furthermore, insufficient physical activity is directly linked to early menarche. External influences such as media exposure shape sexual behaviors, which may accelerate menarche onset. Poor stress management also disrupts estrogen regulation, further contributing to early menarche.